2013
DOI: 10.1016/j.asr.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity in the radiogenic activity of the lunar interior: Inferences from CHACE and LLRI on Chandrayaan-1

Abstract: In the past, clues on the potential radiogenic activity of the lunar interior have been obtained from the isotopic composition of noble gases like Argon. Excess Argon (40) relative to Argon (36), as compared to the solar wind composition, is generally ascribed to the radiogenic activity of the lunar interior. Almost all the previous estimates were based on, 'on the spot' measurements from the landing sites. Relative concentration of the isotopes of 40 Ar and 36 Ar along a meridian by the Chandra's Altitudinal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…It can be seen that the partial pressures show significant variations. This sort of short scale variation seen for 40 Ar has been proposed to be associated with the lunar surface topography (Sridharan et al, 2013a). For the determination of absolute number density of the species, the partial pressures are first converted to the respective number densities at the altitude/latitude using the perfect gas law and the surface temperature at the corresponding latitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the partial pressures show significant variations. This sort of short scale variation seen for 40 Ar has been proposed to be associated with the lunar surface topography (Sridharan et al, 2013a). For the determination of absolute number density of the species, the partial pressures are first converted to the respective number densities at the altitude/latitude using the perfect gas law and the surface temperature at the corresponding latitude.…”
Section: Resultsmentioning
confidence: 99%
“…The sum of the relative amplitudes of different mass constituents has to be normalized to this value and only then individual densities could be estimated. While the significant presence of the heavier species (around 60 and 90 amu) was also detected by CHACE (Sridharan et al, 2013b) the CHACE data further revealed large spatial heterogeneity in the radiogenic activity of the lunar interior inferred using the measurements of the relative composition of the isotopes of Argon (Sridharan et al, 2013a). When the total densities are of the order of 10 6 cm À 3 , the mean free path λ i.e., the distance traveled by any atom or molecule turns out to be (λ ¼1/nσ; where n is the number density and σ is the collision cross section) 43 Â 10 3 km confirming the existence of a surface bound exosphere of the Moon.…”
Section: Introductionmentioning
confidence: 83%
“…The LAMP argon limits are 5% and 38% lower than LACE measurements two-hours before and after the dawn and dusk terminators, respectively, in the comparable local time regions measured by LAMP in LRO's polar orbit. Sridharan et al (2013) published a study on the 40 Ar/ 36 Ar ratio obtained by Chandrayaan-1, but they do not report the 40 Ar density. Finally, preliminary results from the LADEE spacecraft confirmed the detection of argon near the sunrise terminator (Benna et al, 2014a) for the first time after four decades.…”
Section: Current and Past Campaigns To Detect Lunar Exospheric Argonmentioning
confidence: 93%
“…The atmosphere was made of several species of which mass (amu) 18, 44, 17 and 28 were the most dominant. In addition, small but clear signals of mass 36 and 40 were also detected [16]. The mass spectra also revealed several other minor constituents (with some unknown species with mass 94).…”
Section: Lunar Environmentmentioning
confidence: 84%